PENGARUH LEVEL OF DISCLOSURE TERHADAP COST OF EQUITY CAPITAL DENGAN VARIABEL KONTROLDEBT TO EQUITY RATIO, SIZE, BETA DANMARKET TO BOOK VALUE PADA INDEX KOMPAS 100 - Siti Aisyah; Rohmawati Kusumaningtias (Universitas Negeri Malang, 2016)
Level of disclosure is a disclosure of the information provided as an attachmentto the financial statements in the form of footnotes or additional. The main motive of investors to invest is to obtain an optimal return because of certain risks. To obtain optimum returns investors need to assess the condition of the company that became the object of investment is one of them by looking at financial statements in which there is disclosure. This study was conducted to see the influence of the level of disclosure on cost of equity capital firm with a control variable debt to equity ratio, size, beta, and market to book value. This study takes a population index compass 100 companies listed on the Stock Exchange the period of 2008. The method used to determine the sample waspurposive sampling. Samples obtained as many as 41 companies during the study period. Analytical techniques used in this study is multiple regression. The results of simultaneous tests (F test) showed that the level of disclosure, Debt to equity ratio, Size, Beta, Market to book value is significant effect simultaneously on the cost of equity capital. Partial test results showed that the level of disclosure significant positive effect on the cost of equity capital, Debt to equity ratio, a significant negative effect on the cost of equity capital, Size significant negative effect on the cost of equity capital, Beta significant negative effect on the cost of equity capital, Market to book value significantly negative effect on the cost of equity capital, R2 indicates that the variable X (DISCL, DE, SIZE, BETA and MB) can define a variable Y (KS) of 60.57% while 39.43% influenced by other.Keywords: Level of disclosure (DISCL), Debt to equity ratio (DE), Size, Beta, Market to book value (MB) and the cost of equity capital (KS).